A Gateway Deployment Heuristic for Enhancing the Availability of Sensor Grids. (17th July 2016) - Hussain, Majid; Kim, Ki-Hyung; Akbar, Ali Hammad; Khalid, Shehzad; Bang, Seung-Jin; Javed, Mohsin; Amjad, Madiha
Wireless sensor grids form a special class of sensor networks that find more applicability than their randomly deployed counterparts in many commercial applications due to innate regularity in their design and operation. In contemporary wireless sensor grids, primarily single gateway sensor grids, each node senses the information and follows a relay relationship with gateway forming a multisource single receiver paradigm and pursues an added energy consumption pattern that serves as a premier bottleneck in wireless sensor grid environment. This research focuses on statistically modeling the energy consumption of single gateway sensor grids in terms of network availability by analyzing different energy consumption phenomena with communication as a grid-wide routing problem. On the basis of our findings and results in conjunction with Moor's law of semiconductors and batteries, we propose a linear programming heuristic for multiple gateway deployment to reduce network survivability costs and optimize communication for wireless sensor grids. We then present a case study using the proposed heuristic that is augmented through a node scheduler for nearest gateway connectivity, collision avoidance, and fairness, to show the performance gain that presents an ultimate cut-through energy paradigm.